If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 5 = 4m + -15 Reorder the terms: 5 + 8m = 4m + -15 Reorder the terms: 5 + 8m = -15 + 4m Solving 5 + 8m = -15 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 5 + 8m + -4m = -15 + 4m + -4m Combine like terms: 8m + -4m = 4m 5 + 4m = -15 + 4m + -4m Combine like terms: 4m + -4m = 0 5 + 4m = -15 + 0 5 + 4m = -15 Add '-5' to each side of the equation. 5 + -5 + 4m = -15 + -5 Combine like terms: 5 + -5 = 0 0 + 4m = -15 + -5 4m = -15 + -5 Combine like terms: -15 + -5 = -20 4m = -20 Divide each side by '4'. m = -5 Simplifying m = -5
| log[9](7)-log[9](10)=log[9]x | | x^2+-6x+8y+17=0 | | y=14.95+.50(50) | | 9-4(2c-1)= | | 3(-4b)-2(a-b-c)= | | 5q-4=2q+2 | | k=4-k | | -m(2m+2n)+3mn+2m^2= | | 20x+0.50=100x+0.25 | | 8n-2(n^2+n)+12= | | 20x+0.25=100 | | Cos(2t)=sin(t) | | 6x7/5 | | (2y-3)(2y-3)(2y-3)= | | 2.5x+3.75=5x | | =-3.8-1.2 | | 3(-2-2)-1=2-5(-2+5) | | =3.8-1.2 | | f(x)=(x)2+6x+9 | | -3x+15=4.5 | | =(4x+18y)-(-22x+6y) | | 14x+18=275-222 | | x^3+4x-166=0 | | =(3x+16y)-(-23x+5y) | | 4(2+0y)-3y=24 | | 6-23u+20u*2= | | ((x^2-9)/5)-((x^2-4)/15)=(1-2x)/3 | | logx=.4 | | h=16t^2+160t+10 | | (x^2-9/5)-(x^2-4/15)=1-2x/3 | | r-17-1=-4.8 | | =(5x+15y)-(-28x+7y) |